How to Successfully Implement Telework? A Conceptual Framework Proposition - Dhaouadi, Nacef; Aridhi , Eya (Journal of Telecommunications and the Digital Economy, 2025)
Teleworking in the Covid-19 pandemic has become a widespread practice adopted by companies worldwide, providing a unique opportunity to experiment with it on a large scale. This study aimed to elucidate the organisational factors facilitating the successful implementation of telework. The primary objective was to identify the organisational and individual prerequisites, as well as the mediating mechanisms, necessary for the successful establishment of telework and measured by the telework outcomes. To do so, we developed a conceptual model to analyse the factors influencing the success of this transition and we tested it on a sample of 171 employees from the banking, IT, and telecommunication sectors. The results indicate that perceived autonomy, management of work-family conflict, and organisational support are key factors in ensuring employee satisfaction, performance, and engagement within this new work framework. However, telework does not have a direct impact on these outcomes without mediating mechanisms.